2009
DOI: 10.1002/anie.200901621
|View full text |Cite
|
Sign up to set email alerts
|

One‐Dimensional Gold Nanoparticle Arrays by Electrostatically Directed Organization Using Polypeptide Self‐Assembly

Abstract: The study of interactions between particles organized in a linear configuration is interesting from a quantum mechanical perspective, and the anisotropic properties of linear assemblies is of potential interest for the development of solid-state devices. [1][2][3] This anisotropy may be manifested as a difference in the magnetization and coercivity obtained in a magneticnanoparticle array when a field is applied along the chain or orthogonal to it. [4,5] Nonlinear electrical characteristics [3] or dichroism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 57 publications
0
52
0
Order By: Relevance
“…Since the oligomerization state of VW05 has been studied before [30], the DLS spectrum of VW05 was used as a reference for all other peptides. All measurements were performed at a sample concentration of 15 µM at pH 9 and pH 11 because the net charge of the peptides switches from positive to negative within this pH range.…”
Section: Resultsmentioning
confidence: 99%
“…Since the oligomerization state of VW05 has been studied before [30], the DLS spectrum of VW05 was used as a reference for all other peptides. All measurements were performed at a sample concentration of 15 µM at pH 9 and pH 11 because the net charge of the peptides switches from positive to negative within this pH range.…”
Section: Resultsmentioning
confidence: 99%
“…It was also shown that the histidine tag plays a solubilizing role when it is charged, in addition to its conventional function in protein purification and its observed role in the immobilization of negatively charged nanoparticles. 81 At acidic pH (upon protonation of glutamic acid residues), the polypeptide and the conjugates formed aggregates with elongated or spherical morphologies depending on the nature and length of the hydrophilic block. Although only a few examples were shown in this study, our results clearly illustrate that a combination of recombinant synthesis and chemical conjugation methods may offer a wide spectrum of nanostructures with controlled size and morphology by the precise control of the block composition.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,11 In particular, fabrication of linear assemblies of inorganic elements is of great interest for the development of nano-devices due to their anisotropic properties in 1-dimensional state. 16 For that purpose, carbon nanotubes are excellent template for the fabrication of linear assembly of inorganic elements. 17,18 In addition, biomolecules such as DNA, 19 peptides, 16 and viruses 20 were used as a template for the organization of nanoparticles.…”
mentioning
confidence: 99%
“…16 For that purpose, carbon nanotubes are excellent template for the fabrication of linear assembly of inorganic elements. 17,18 In addition, biomolecules such as DNA, 19 peptides, 16 and viruses 20 were used as a template for the organization of nanoparticles. Self-assembled organic nanotubes are particularly advantageous as a template for the linear organization of nanoparticles because the surface anchoring functionality can be efficiently tailored.…”
mentioning
confidence: 99%
See 1 more Smart Citation